Increasing smoke alarm operability through theory-based health education: a randomised trial - Miller, Ted; Bergen, G.; Ballasteros, M.; Battacharya, S.; Gielen, A.; Sheppard, M. (BMJ Publishing, 2014)
Background - Although working smoke alarms halve deaths in residential fires, many households do not keep alarms operational. We tested whether theory-based education increases alarm operability. Methods - Randomised multiarm trial, with a single arm randomly selected for use each day, in low-income neighbourhoods in Maryland, USA. Intervention arms: (1) Full Education combining a health belief module with a social-cognitive theory module that provided hands-on practice installing alarm batteries and using the alarm's hush button; (2) Hands-on Practice social-cognitive module supplemented by typical fire department education; (3) Current Norm receiving typical fire department education only. Four hundred and thirty-six homes recruited through churches or by knocking on doors in 2005–2008. Follow-up visits checked alarm operability in 370 homes (85%) 1–3.5 years after installation. Main outcome measures: number of homes with working alarms defined as alarms with working batteries or hard-wired and number of working alarms per home. Regressions controlled for alarm status preintervention; demographics and beliefs about fire risks and alarm effectiveness. Results - Homes in the Full Education and Practice arms were more likely to have a functioning smoke alarm at follow-up (OR=2.77, 95% CI 1.09 to 7.03) and had an average of 0.32 more working alarms per home (95% CI 0.09 to 0.56). Working alarms per home rose 16%. Full Education and Practice had similar effectiveness (p=0.97 on both outcome measures). Conclusions - Without exceeding typical fire department installation time, installers can achieve greater smoke alarm operability. Hands-on practice is key. Two years after installation, for every three homes that received hands-on practice, one had an additional working alarm.